2004
DOI: 10.1203/01.pdr.0000139713.64264.bc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citrin Deficiency in the Perinatal Period: Feasibility of Newborn Mass Screening for Citrin Deficiency

Abstract: Deficiency of citrin due to mutations of the SLC25A13 gene causes adult-onset type II citrullinemia (CTLN2) and one type of neonatal intrahepatic cholestasis (NICCD). About half of the NICCD patients are detected based on high galactose, phenylalanine, and/or methionine concentrations on newborn mass screening (NMS). To clarify the perinatal and neonatal effects and the inconsistent results on NMS, we examined aminograms, the levels of bile acids and galactose in dried blood spots for NMS from 20 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 27 publications
2
50
1
Order By: Relevance
“…The design is different from those of the previous studies in which mutation analysis was generally only carried out on individuals for whom a diagnosis of citrin deficiency is highly suspected based on citrullinemia detected by MS analysis [6,20,[32][33][34][35][36][37][38][39]. In contrast, we tested all cases of various forms of aminoacidemia, including those patients with citrulline in normal range and those who were given a possible diagnosis of tyrosinemia or aminoacidemia secondary to liver diseases on the basis of MS amino acid analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design is different from those of the previous studies in which mutation analysis was generally only carried out on individuals for whom a diagnosis of citrin deficiency is highly suspected based on citrullinemia detected by MS analysis [6,20,[32][33][34][35][36][37][38][39]. In contrast, we tested all cases of various forms of aminoacidemia, including those patients with citrulline in normal range and those who were given a possible diagnosis of tyrosinemia or aminoacidemia secondary to liver diseases on the basis of MS amino acid analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoacidemia is one of the more important features of NICCD, but the diagnosis is difficult without early monitoring of amino acid levels [24]. MS to detect citrin deficiency is useful in identifying the clinical course, treatment, and prevention of this disease [38]. In this study, citrin deficiency was not only found in patients with citrullinemia, but also in patients with aminoacidemia other than citrullinemia, suggesting that although citrullinemia is a very useful parameter for the diagnosis of citrin deficiency, the diagnosis cannot be ruled out even if the level of citrulline is within normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Since almost all NICCD patients tested show increased citrulline levels in the blood at 1 month of age (Tamamori et al 2004), tandem mass measurement of amino acids, including citrulline, helps to diagnose NICCD patients (Shigematsu et al 2002). The frequency of homozygotes in Japan (1/19,000) calculated from the carrier rate ) is almost the same as the NICCD incidence (Shigematsu et al 2002) but quite different from CTLN2 incidence (1/100,000 to 1/230,000) (Nagata et al 1991;Kobayashi et al 1993).…”
Section: The Origin Of Mutation [I] or [Ii] Alleles In East Asia Postmentioning
confidence: 98%
“…Adult-onset type II citrullinemia is characterized by the sudden appearance of behavioral aberrations, restlessness, disorientation, and coma, which can occur at any age (11-79 years) in life, but usually occurs in adulthood [1,3,4,7,[9][10][11]. However, NICCD is characterized by intrahepatic cholestasis and shows milder symptoms without specific treatment [5,8,[12][13][14][15][16][17], except in some cases [15]. Some of the individuals carrying SLC25A13 gene mutations in both alleles, however, may develop CTLN2 with neuropsychiatric symptoms several decades later [9,11,14].…”
Section: Introductionmentioning
confidence: 99%